Evaluating biotic and abiotic drivers of avian community mobbing responses along urban gradients in Southern California - Benjamin Ewing; Eric M. Wood; Ari Martínez (Ecosphere)
Abstract Urbanization is a significant pressure affecting wildlife and has the potential to greatly alter behavioral responses in animal communities. A behavioral response that is potentially affected by urbanization is the mobbing of predators by potential avian prey species. We tested three hypotheses concerning the effects of various abiotic and biotic factors in influencing avian mobbing responses along an urban–rural gradient. We conducted predator simulations by using playback of the vocalizations of the Western Screech‐owl, Megascops kennicottii, which is a predatory species that elicits a mobbing response from other birds. These vocalizations, accompanied by stuffed models of the screech‐owls, were broadcast at a variety of points along an urban–rural gradient in Los Angeles and Orange Counties in Southern California. We used an experimental approach using playback, that is, vocalization and models, to investigate whether mobbing responses of birds change in areas where predators may be naturally present (high vegetation density) or absent (high impervious cover). We recorded the number of individual birds and species that exhibited mobbing behavior at experimental sites, as well as various biotic and abiotic factors that may influence avian mobbing, including noise level, impervious surface cover, avian community turnover across the urban‐to‐rural gradient, and the structure of local vegetation, which we assumed may be important for either hosting roosting screech‐owls or providing cover for mobbing bird species. For both the number of mobbing individuals and species, we showed that mobbing responses decreased with increasing noise levels and percentage of impervious surfaces and increased with increasing woody vegetation. There was some evidence that predator presence influenced mobbing responses. Our results show that the changes associated with urbanization can significantly alter antipredator behavior in birds, and that these changes can alter avian social eavesdropping networks.